THE INFLUENCE OF KNOWLEDGE SHARING AND CREATIVE WORK ON INNOVATIVE BEHAVIOR - Bagas Rahman Gumelar; Anjelina Deliyanni (Universitas KH. Abdul Chalim Mojokerto, 2025)
The purpose of this analysis is to determine the effect of knowledge sharing and creative work climate on innovative behavior, with a quantitative approach and cross-sectional time horizon method. The research was conducted in 12 schools in Cirebon City, involving 142 respondents obtained through the distribution of questionnaires. Based on the results, innovative knowledge sharing practices, positive and creative work climate, and innovative teacher behavior were significantly correlated. This suggests that creating a climate that supports creativity and knowledge sharing among teachers can encourage innovation, and this is crucial for improving learning effectiveness. Therefore, schools need to develop policies that encourage collaboration, knowledge sharing, and create an innovative and creative work climate. These measures will not only improve the quality of teaching but also have an impact on improving student achievement, creating a productive and thriving educational environment.